Inovasi Pengelolaan Limbah Minyak Jelantah Menjadi Lilin Aroma Sebagai Solusi Usaha Masyarakat Desa Jatirejo Kabupaten Kendal - Reni Widiana Ningsih; Anggifatul Hana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Processing used cooking oil into aroma candles is an innovation that provides a sustainable business solution for rural areas. Used cooking oil, usually considered household waste, can be converted into economically valuable products such as aroma candles. The process involves filtering, refining, mixing with ingredients such as stearin, colorants, and fragrances, and forming candles in various shapes and attractive scents. In addition to increasing the economic value of the village community, this business also reduces used cooking oil waste that can pollute the environment. With small capital and simple technology, this process can empower villagers, create employment opportunities, increase income, and support environmentally friendly practices. Training and education programs on entrepreneurship and waste management can also grow the business, strengthen the local economy, and raise awareness about the importance of protecting the environment.